Urothelial carcinoma arising from the transplanted kidney: A single‐center experience and literature review. Issue 6 (23rd April 2019) - Bellini, Maria Irene; Gopal, Jeevan Prakash; Hill, Peter; Nicol, David; Gibbons, Norma
Abstract: Urothelial carcinoma (UC) is a malignancy predominantly arising in the bladder. Upper tract UC (UUC) is uncommon, accounting only for 5‐10% of the cases. High incidence of neoplasms is associated with immunosuppressive therapy; thus, UCs of the transplanted grafts often lead to a more aggressive treatment, in order to withdraw completely the immunosuppression. It significantly affects the patient quality of life, meaning return to dialysis, along with the worse life expectancy. We present our single‐institution experience of this rare malignancy in two mid‐age kidney transplant recipients, with UCs successfully treated with radical nephroureterectomy: G3 pT3 N0 + G3 pT1 N0 in the first patient and G3 pT2 N0 in the second one. We also review the previous literature focusing on stage of presentation and treatment for the affected kidney transplant patients.